The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.2147/ijgm.s355974
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Systemic Diseases on Olfactory Function in COVID-19 Infected Patients

Abstract: Background COVID-19 (SARS-CoV-2/2019-nCoV) is now a major public health threat to the world. Olfactory dysfunctions (ODs) are considered potential indicating symptoms and early case identification triaging for coronavirus disease 2019 (COVID-19). The most common reported comorbidities are diabetes mellitus, chronic lung disease, and cardiovascular disease. The objective of this study was to evaluate prevalence of different types of smell disorders in patients with laboratory-confirmed COVID-19 inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Taste and smell disturbances are commonly described as COVID-19 post-acute sequelae (63) even in population under 21 years old, and these can last for 2 years after acute infection (64). In adults, this has been associated with chronic systemic conditions (65)(66)(67), and correlated with particular acute COVID-19 symptoms (68). Nevertheless, the precise etiopathogenesis of this disorder is still elusive (69, 70).…”
Section: Discussionmentioning
confidence: 99%
“…Taste and smell disturbances are commonly described as COVID-19 post-acute sequelae (63) even in population under 21 years old, and these can last for 2 years after acute infection (64). In adults, this has been associated with chronic systemic conditions (65)(66)(67), and correlated with particular acute COVID-19 symptoms (68). Nevertheless, the precise etiopathogenesis of this disorder is still elusive (69, 70).…”
Section: Discussionmentioning
confidence: 99%
“…UGT2A1 and UGT2A2 are part of a family of enzymes that partake in the elimination of odorant particles and may play a role in the physiology of infected cells. Risk factors for OD include current smoking [50], history of allergy [50], female sex [51][52][53][54], younger age group [54,55], Caucasian [39,54], and presence of chronic cardiovascular diseases such as hypertension and diabetes [55].…”
Section: Susceptibilitymentioning
confidence: 99%
“…A retrospective cohort study demonstrated that the presence of anosmia was associated with lower rates of mortality and admission to the ICU in patients. The presence of other symptoms, such as headache, was associated with lower mortality in patients with SARS-CoV-2 infection [5][6][7] .…”
Section: Introductionmentioning
confidence: 95%